18F‐AV‐1451 uptake differs between dementia with lewy bodies and posterior cortical atrophy. Issue 3 (7th January 2019) - Nedelska, Zuzana; Josephs, Keith A.; Graff‐Radford, Jonathan; Przybelski, Scott A.; Lesnick, Timothy G.; Boeve, Bradley F.; Drubach, Daniel A.; Knopman, David S.; Petersen, Ronald C.; Jack, Clifford R.; Lowe, Val J.; Whitwell, Jennifer L.; et al.
Abstract: Background: Posterior cortical atrophy and dementia with Lewy bodies are 2 distinct clinical syndromes, yet they can overlap in symptoms and occipital hypometabolism. Patients with dementia with Lewy bodies often have overlapping Alzheimer's disease pathology. Similarly, Lewy bodies can be found in patients with posterior cortical atrophy. We investigated differences in the distribution and magnitude of F18‐AV‐1451 uptake in patients with these 2 syndromes. Methods: Consecutive patients with probable dementia with Lewy bodies (n = 33), posterior cortical atrophy (n = 18), and cognitively unimpaired controls (n = 100) underwent 18 F‐AV‐1451 positron emission tomography. Regional differences in AV‐1451 uptake were assessed using voxel‐wise and an atlas‐based approach. The greatest differences in AV‐1451 uptake between patient groups were identified using area under receiver operating curve statistics, and a composite region was derived. Results: AV‐1451 uptake in both patient groups was predominantly localized to the lateral occipital regions, but the magnitude of uptake was markedly greater in posterior cortical atrophy compared with dementia with Lewy bodies. The posterior cortical atrophy group showed the greatest AV‐1451 uptake throughout all the gray matter compared with that in other groups. The occipital composite region, consisting of superior, middle, and inferior occipital cortices, distinguished posterior cortical atrophy from dementia with Lewy bodies (area under the curve >0.97; P < 0.001, Bonferroni‐corrected) with excellent sensitivity (88%) and specificity (100%). Conclusions: Posterior cortical atrophy and dementia with Lewy bodies can share clinical features, and although the pattern of AV‐1451 uptake in occipital cortices overlaps between these 2 syndromes, its magnitude is significantly higher in posterior cortical atrophy. © 2019 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.